Differences in pediatric and adult epilepsy surgery: A comparison at one center from 1990 to 2014. (21st December 2018) - Cloppenborg, Thomas; May, Theodor W.; Blümcke, Ingmar; Fauser, Susanne; Grewe, Philip; Hopf, Johanna L.; Kalbhenn, Thilo; Polster, Tilman; Schulz, Reinhard; Woermann, Friedrich G.; Bien, Christian G.
Summary: Objective: Surgical volumes at large epilepsy centers are decreasing. Pediatric cohorts, however, show a trend toward more resections and superior outcome. Differences in pediatric and adult epilepsy surgery were investigated in our cohort. Methods: The Bethel database between 1990 and 2014 was retrospectively analyzed. Results: A total of 1916 adults and 1300 children underwent presurgical workup. The most common etiologies were medial temporal sclerosis (35.4%) in adults, and focal cortical dysplasias (21.1%) and diffuse hemispheric pathologies (14.7%) in children. Only 1.4% of the total cohort had normal histopathology. A total of 1357 adults (70.8%) and 751 children (57.8%) underwent resections. Surgery types for children were more diverse and showed a higher proportion of extratemporal resections (32.8%) and functional hemispherectomies (20.8%). Presurgical evaluations increased in both groups; surgical numbers remained stable for children, but decreased in the adult group from 2007 on. The patients' decision against surgery in the adult nonoperated cohort increased over time (total = 44.9%, 27.4% in 1995‐1998 up to 53.2% in 2011‐2014; for comparison, in children, total = 22.1%, stable over time). Postsurgical follow‐up data were available for 1305 adults (96.2%) and 690 children (91.9%) 24 months after surgery. The seizure freedom rate was significantly higher in children than in adults (57.8% vs 47.5%, P < 0.001) and significantly improved over time ( P = 0.016). Significance: Pediatric epilepsy surgery has stable surgical volumes and renders more patients seizure‐free than epilepsy surgery in adults. A relative decrease in hippocampal sclerosis, the traditional substrate of epilepsy surgery, changes the focus of epilepsy surgery toward other pathologies.